2015
DOI: 10.1016/j.csr.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Hurricane Sandy on the shoreface and inner shelf of Fire Island, New York: Large bedform migration but limited erosion

Abstract: 14We investigate the impact of superstorm Sandy on the lower shoreface and inner shelf 15 offshore the barrier island system of Fire Island, NY using before-and-after surveys involving 16 swath bathymetry, backscatter and CHIRP acoustic reflection data. As sea level rises over the 17 long term, the shoreface and inner shelf are eroded as barrier islands migrate landward; large 18 storms like Sandy are thought to be a primary driver of this largely evolutionary process. The 19 "before" data were collected in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…() and Goff et al . () off Fire Island. Bathymetry is derived from National Geophysical Data Center (NGDC) Coastal Relief Model ( http://www.ngdc.noaa.gov/mgg/coastal/startcrm.htm).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…() and Goff et al . () off Fire Island. Bathymetry is derived from National Geophysical Data Center (NGDC) Coastal Relief Model ( http://www.ngdc.noaa.gov/mgg/coastal/startcrm.htm).…”
Section: Introductionmentioning
confidence: 99%
“…(A) Sustained wind speeds and (B) significant wave height from 2000 through to 2013 at National Oceanic and Atmospheric Administration (NOAA) buoy 44025 ( http://www.ndbc.noaa.gov/station_page.php?station=44025); modified after Goff et al . (). See Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oceanographic and geologic investigations along Fire Island have focused on the aspects of SFCR maintenance (Warner et al, ) and SFCR effects on evolution of Fire Island coast (Kana et al, ; Lentz et al, ; List et al, ; Rosati et al, ; Schwab et al, ; Swift et al, ). Fire Island has recently been subject to increasing attention also due to the impact of Hurricane Sandy in October 2012 (Goff et al, ; Schwab et al, ; Warner et al, ) which identified the need to further understand the variations of impacts from storm events.…”
Section: Introductionmentioning
confidence: 99%
“…J.C. Warner et al Continental Shelf Research 138 (2017) 1-18 Understanding the form and magnitude of seafloor morphologic change is critical to developing coastal sediment budgets, as well as increasing our knowledge of how these processes are time-integrated into the decadal and longer timescales of continental margin sedimentation (e.g., Riggs et al, 1995;Schwab et al, 2013;Miselis and McNinch, 2006;Denny et al, 2013). Observations of impacts to the seafloor in the coastal zone (including shoreface and inner continental shelf) from hurricanes are sparse due to the logistical and technological difficulty in data collection required for measuring seafloor changes (e.g., Goff et al, 2015;Schwab et al, 2016). Observations of oceanographic and sediment transport conditions during hurricanes are also typically rare, and often observed by chance (Wren and Leonard, 2005;Teague et al, 2007).…”
Section: Introductionmentioning
confidence: 99%